Assessment of results of functional units department of marketing - D.V. Raiko (Marketing i Menedžment Innovacij, 2011)
Improved methodological support of the evaluation of heads of departments of marketing, the distinction which is urahuvanni functional orientation of each department, the application of expert methods using universal scale Harinhtona for the quantitative determination of performance in two components: the results of the work and qualities of leaders (business, professional and personal). The total score corresponds to the head of qualitative features of the low to very high, which allows to make personnel decisions for the promotion of leaders and motivating material as well as identify priority areas to improve the results of their work and improving the professional, business, personal qualities.